High performance computing in science and engineering : second International Conference, HPCSE 2015, Soláň, Czech Republic, May 25-28, 2015, Revised selected papers /: second International Conference, HPCSE 2015, Soláň, Czech Republic, May 25-28, 2015, Revised selected papers. (2016) - Unknown
No abstract available